The role of gender in the International Conference on Pervasive Computing and Communications - Peltonen, Ella (Frontiers in Computer Science, 2022)
The International Conference on Pervasive Computing and Communications (IEEE PerCom) is a CORE 2021 A* conference (top 7% of ranked venues) that aims to present scientific advances in a broad spectrum of technologies and topics in ubiquitous/pervasive computing, including wireless networking, mobile and distributed computing, sensor systems, ambient intelligence, and smart devices. During the last couple of years, the PerCom organization committee has successfully included many prestigious female researchers to submit, participate, and organize the conference. However, there is still work to do and to help the progress, this article analyses the history of the conference from a gender perspective. This article goes through accepted articles of the last 20 years of the Percom conferences, showing that even if the role of female authors, in general, has increased, more first and leading female researchers should still be welcomed in the community. Through this analysis, this article aims to highlight the role of gender in the conference program and seeks to find trends and possible improvements to achieve a broader gender balance in pervasive computing.